Recovery From Opioid Use Disorder (OUD) After Monthly Long-acting Buprenorphine Treatment: 12-Month Longitudinal Outcomes From RECOVER, an Observational Study - Ling, Walter (J Addict Med, 2020)
While evidence has mounted regarding the short-term effectiveness of pharmacotherapy for opioid use disorder (OUD), little is known about longer-term psychosocial, economic, and health outcomes. We report herein 12-month outcomes for an observational study enrolling participants who had previously taken part in a long-acting buprenorphine subcutaneous injection (BUP-XR) trial for moderate to severe OUD. METHODS: The RECOVER (Remission from Chronic Opioid Use: Studying Environmental and SocioEconomic Factors on Recovery; NCT03604861) study enrolled participants from 35 US community-based sites. Self-reported sustained opioid abstinence over 12 months and self-reported past-week abstinence at 3-, 6-, 9-, and 12-month visits were assessed. Multiple regression models assessed the association of BUP-XR duration with abstinence, controlling for potential confounders. Withdrawal, pain, health-related quality of life, depression, and employment at RECOVER baseline and 12-month visits were also compared to values collected before treatment in the BUP-XR trial. RESULTS: Of 533 RECOVER participants, 425 completed the 12-month visit (average age 42 years; 66% male); 50.8% self-reported sustained 12-month and 68.0% past-week opioid abstinence. In multiple regressions, participants receiving 12-month versus ≤2-month BUP-XR treatment duration had significantly higher likelihood of sustained opioid abstinence (75.3% vs 24.1%; P = 0.001), with similar results for past-week self-reported abstinence over time. During RECOVER, participants had fewer withdrawal symptoms, lower pain, positive health-related quality of life, minimal depression, and higher employment versus pre-trial visit. CONCLUSIONS: RECOVER participants reported positive outcomes over the 12-month observational period, including high opioid abstinence and stable or improved humanistic outcomes. These findings provide insights into the long-term impact of pharmacotherapy in OUD recovery.